2002
DOI: 10.1046/j.1468-3083.2002.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Imiquimod 5% cream is an acceptable treatment option for external anogenital warts in uncircumcised males

Abstract: Imiquimod cream at a dosing regimen of three times per week, is effective and has an acceptable safety profile in the treatment of prepuce associated warts and other external anogenital warts in uncircumcised males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In general, the patients with more difficult warts are more likely to receive additional therapy. Multiplicity and the total treatment period were thought to reflect the therapeutic difficulties21. To take into account the therapeutic difficulties, such as the number of lesions and the treatment period, covariant analysis was performed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the patients with more difficult warts are more likely to receive additional therapy. Multiplicity and the total treatment period were thought to reflect the therapeutic difficulties21. To take into account the therapeutic difficulties, such as the number of lesions and the treatment period, covariant analysis was performed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…cryogen spray versus cotton ball application) and treatment intervals2. When the spray gun is used, it is held perpendicular to the wart at a distance of 1~2 cm and liquid nitrogen is sprayed until the ice ball has spread from the center to include the edge of the wart and a 2 mm margin21. The lesion is then allowed to thaw.…”
Section: Discussionmentioning
confidence: 99%
“…A more restricted total wart area probably represents a reduced viral load and predicts a favourable response. The clearance of genital warts has been related before to the size and number of lesions 5–7 . However, other authors have not found an association between the number of anogenital warts and the clinical outcome 8 …”
Section: Discussionmentioning
confidence: 99%
“…25 More restricted total wart area probably represents a reduced viral load and predicts a favourable response. However, the data from the literature are contradictory; because whereas some investigators have found an association between the clearance of genital warts and the size and number of lesions, 26 …”
Section: Discussionmentioning
confidence: 99%